Confounding Factors Affecting the National Institutes of Health (NIH) Chronic Graft-Versus-Host Disease Organ-Specific Score and Global Severity - Aki, Sahika Zeynep (Bone Marrow Transplant, 2016)
The 2005 NIH chronic graft-versus-host disease (cGVHD) organ severity is based on the assessment of current status regardless of whether abnormalities are due to GVHD. The score assignment does not require knowledge of past manifestations, attribution, or whether cGVHD is still active. The aim of this study is to describe confounding factors affecting organ scores in patients with cGVHD. The study included 189 consecutive cGVHD patients evaluated at our center in 2013. Providers completed the NIH 0–3 organ-specific scoring evaluation with two questions added for each organ to identify abnormalities that were 1) not attributed to cGVHD, or 2) attributed to cGVHD plus other causes. Abnormalities attributed to causes other than GVHD were recorded. Eighty (14%) abnormalities were not attributed to cGVHD in at least one organ, and 41 (7%) abnormalities were attributed to cGVHD plus other causes in at least one organ. A total of 436 (78%) abnormalities were attributed only to cGVHD. Abnormalities not attributed to cGVHD were observed most frequently in the lung, gastrointestinal tract and skin. Most common abnormalities included pre-transplant condition, sequelae from GVHD, deconditioning, infections and medications. Our results support the the 2014 NIH consensus recommendation to consider attribution when scoring organ abnormalities.